Optimization Of Simultaneous Estimation Of Candesartan And Nifedipine In Combination Therapy For Hypertension Management: A Green HPLC Approach Using Design Of Experiment Methodology - Darshil B Shah; Dr. Bhavesh H. Patel; Dr. Jignesh S. Shah (Journal of Advanced Zoology, 2024)
ackground: Hypertension is a prevalent health condition with severe implications for cardiovascular health. Combination therapy involving Candesartan and Nifedipine has emerged as a promising approach for managing hypertension due to the synergistic effects of these medications. Methods: This study aimed to develop a Design of Experiment (DoE) based Green High-Performance Liquid Chromatography (HPLC) method for the simultaneous estimation of Candesartan and Nifedipine in a combined dosage form. Reversed-phase HPLC was utilized with UV-Vis spectrophotometry for detection. DoE principles were applied to optimize chromatographic conditions, including pH, ethanol percentage in the mobile phase, and flow rate. Results: Optimal chromatographic separation was achieved using a composite mobile phase comprising ethanol and potassium dihydrogen phosphate buffer (45:55, v/v) at pH 3.7, with a flow rate of 1 mL/min. Statistical analysis confirmed the significance of these parameters in achieving efficient separation. The developed method exhibited high precision, accuracy, and reliability across various validation parameters, including specificity, linearity, repeatability, and robustness. Conclusion: The proposed DoE-based Green HPLC method offers a sustainable and efficient approach for the simultaneous estimation of Candesartan and Nifedipine in hypertension management. By integrating green chemistry principles with systematic method development, this method provides a reliable analytical tool for routine quality control purposes in pharmaceutical formulations containing these medication